THE DISMISSAL OF PRESIDENT JUAN DE DIOS MARTÍNEZ MERA IN 1933: RIOBAMBA, AN IMPORTANT POLITICAL COLLECTIVE - Yerbabuena Torres, Carlos Fernando (2024)
Juan de Dios Martínez Mera, president of Ecuador, resigned from his position on October 14, 1933, amid a series of popular protests. He was accused of coming to power fraudulently, not promoting suffrage freedom, and not representing the ideals of the Ecuadorian people. In this context, the article analyzes the role of political collectives in Riobamba as fundamental actors in the downfall of the president. The uprisings against the regime originated in this city, and the idea of removal was conceived by the Congress, aspects that have been overlooked or treated very lightly by national history. This work is carried out using the historical method and is framed within the theoretical proposal of Agustín Cueva, who argues that in Ecuador in the thirties, a crisis of hegemony became evident.